Polycentric governance of commons through multi-stakeholder platforms: Insights from two case studies in India - ElDidi, Hagar; Rawat, Shivanyaa; Meinzen-Dick, Ruth S.; Chaturvedi, Rahul; Sanil, Richu (Springer, 2025)
This paper examines the complexities of commons governance, focusing on the role of multistakeholder platforms (MSPs) in addressing tensions among diverse decision-making centers. Drawing on the experiences of the Indian NGO Foundation for Ecological Security (FES) in Gujarat and Odisha, the study analyzes two MSPs operating at the block level, engaging communities, government, and private sector actors. Through surveys, interviews, and analysis of institutional reports, the research identifies key benefits of MSPs, including enhanced multi-stakeholder engagement, scale, and enabling conditions. It argues that MSPs can effectively support polycentric governance by facilitating inter-community collaboration, strengthening local voices, and building trust over time. The study also underscores the importance of external actors like NGOs in supporting community agency and fostering collaboration across different governance levels.